Socio-economic development and its impact on health personnel in regions of Visegrad Group Plus countries - Ingrid Majerová (Review of Economic Perspectives, 2019)
The quality of life and economic development of economies and their regions is influenced by socio-economic indicators such as unemployment, healthcare and education, environmental issues or household equipment. The question remains whether these indicators within regions can also influence each other and whether they have positive or negative effects. The paper aims to describe the impact of the selected socioeconomic indicators on health personnel, which was also divided from the gender perspective. For this purpose, the regions of the Visegrad Group Plus countries at NUTS II level were selected. The research was performed in the period from 2004 to 2013. According to our results based on the Generalized Method of Moments with panel data, we found out that a change in household income and a change in the number of vehicles in the monitored regions have the greatest (positive) impact on staff in hospitals. The research may contribute to the discussion about levels of regional economic development and the related competitiveness in terms of the socio-economic approach, and it may also provide a basis for further discussion on its measurement and use of appropriate indicators.
Keywords: C33; O15; R11; 330; countries of Visegrad Group Plus; Generalized Method of Moments; health personnel; socio-economic indicators